(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article is a translation of currently relevant scientific and technical terms some problems and their causes are explained. Not only students, but also students in the translation of truly scientific and technical texts experts also face several difficulties, because in translation learning the terms of that field along with a set of common words importance is said.